Comparing Rates of Radiographic Baseplate Loosening Between Cement and Cementless INFINITY Total Ankle Prostheses - Ian Millstein BA; Adel Mahjoub MD; Manisha Koneru MS; Pietro Gentile BS; Erik Freeland DO (Foot & Ankle Orthopaedics, 2023)
Category: Ankle Arthritis Introduction/Purpose: Total ankle replacement has risen in popularity as the contemporary treatment-of-choice for end-stage ankle osteoarthritis. INFINITY™ Total Ankle System (Stryker, Kalamazoo, MI) is one of the most frequently used ankle prostheses. Prior studies established positive functional outcomes; however, aseptic baseplate loosening has reported to occur in approximately one-third of patients. Aseptic baseplate loosening is seen radiographically either as shift in talar or tibial components or evidence of periprosthetic lucency. Aseptic baseplate loosening with persistent pain defines prosthesis failure, thus an indication for early surgical revision. Implementing bone cement may fixate and stabilize prostheses, potentially reducing incidence of aseptic baseplate loosening. This study aimed to determine if patients with cemented INFINITY total ankle prostheses had different incidence of aseptic baseplate loosening than those with cementless prostheses. Methods: Patients who underwent total ankle arthroplasty using the INFINITY total ankle prosthesis system between January 2016 and May 2022 (n = 28) were retrospectively identified using keyword search for “infinity” and Current Procedural Terminology (CPT) code 27702. Fourteen patients had prostheses affixed with cement, and fourteen patients had prostheses that were not cemented. Preoperative, immediate postoperative, and most recently available anteroposterior (AP), mortise, and lateral ankle X- rays were reviewed. Tibiotalar angle, talar tilt, and presence of visible postoperative lucency were assessed independently by two reviewers. Wilcoxon rank-sum test on quantitative variables and chi-square test on categorical variables were performed with 0.05 significance level. Results: Inter-rater reliability was above 94% for all measurements. Comparing the cemented to cementless sample group, difference in average age (59.5 years vs. 56.5 years, p=0.32) and sex (57.1% vs. 50.0% female, p=0.70) were not statistically significant. Pre-operative and immediate post-operative tibiotalar and talar tilt angles were not statistically significantly different between cement and cementless groups (p>0.31 for all comparisons). Only one patient in the cement group had evidence of periprosthetic lucency in the immediate postoperative period. Median follow-up was 362.5 days and 544.5 days in the cement and cementless group, respectively (p=0.52). Follow-up tibiotalar angles and talar tilt angle between cement and cementless groups were not significantly different (p>0.51 for all comparisons). Periprosthetic lucency occurred in 50% of both groups in the follow- up period (p=1.0). Conclusion: Patients with cemented INFINITY total ankle prostheses had equal incidence of aseptic baseplate loosening compared to patients with cementless prostheses. Continuing to examine methods for reducing incidence of baseplate loosening is significant for potentially reducing rate of early prosthesis revision and prosthesis failure, consequently improving quality of life for patients.